2015
DOI: 10.1590/2237-6089-2015-0011
|View full text |Cite
|
Sign up to set email alerts
|

Attentional bias modification based on visual probe task: methodological issues, results and clinical relevance

Abstract: Introduction: Attentional bias, the tendency that a person has to drive or maintain attention to a specific class of stimuli, may play an important role in the etiology and persistence of mental disorders. Attentional bias modification has been studied as a form of additional treatment related to automatic processing. Objectives: This systematic literature review compared and discussed methods, evidence of success and potential clinical applications of studies about attentional bias modification (ABM) using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(45 citation statements)
references
References 77 publications
0
30
0
1
Order By: Relevance
“…Research studies have conclusively demonstrated positive relationships between this form of educator support (Prensky, ; Pape et al, ), and scholastic self‐determination (Abeysekera and Dawson, ; Barrett et al, ), and engagement (Hansen, ; Bradley et al, ; Brass et al, ). The practice of AST also contributes to the development of IM by providing a rationale for choices (Tai et al, ; Queen and Hess, ), empathizing with the perspectives of students (Ten Cate et al, ; Hickman et al, ), and minimizing the use of controlling language (Mohr et al, ; Lopes et al, ; Meza et al, ) in the teaching environment. These practices provide students with the opportunity to pursue unique individual goals (Woolley and Fishbach, ) and interests (Ezell et al, ; Agius et al, ), and satisfy their needs for autonomy (Woolley and Fishbach, ) and competence (Desy et al, ; Gauer and Jackson, ).…”
Section: Theoretical Basis Of Intrinsic Motivationmentioning
confidence: 99%
See 2 more Smart Citations
“…Research studies have conclusively demonstrated positive relationships between this form of educator support (Prensky, ; Pape et al, ), and scholastic self‐determination (Abeysekera and Dawson, ; Barrett et al, ), and engagement (Hansen, ; Bradley et al, ; Brass et al, ). The practice of AST also contributes to the development of IM by providing a rationale for choices (Tai et al, ; Queen and Hess, ), empathizing with the perspectives of students (Ten Cate et al, ; Hickman et al, ), and minimizing the use of controlling language (Mohr et al, ; Lopes et al, ; Meza et al, ) in the teaching environment. These practices provide students with the opportunity to pursue unique individual goals (Woolley and Fishbach, ) and interests (Ezell et al, ; Agius et al, ), and satisfy their needs for autonomy (Woolley and Fishbach, ) and competence (Desy et al, ; Gauer and Jackson, ).…”
Section: Theoretical Basis Of Intrinsic Motivationmentioning
confidence: 99%
“…It has been proposed that an underlying cause for burnouts in health care students is the result of a fear of the demands of the course that lead to an instinctual fight or flight reaction (Robotham and Julian, ). Considering that stress does not have a linear progression or regression (Jacobs et al, ; van Gessel et al, ), and the stigma associated with mental health issues (Lopes et al, ; Luthar, ), this endeavor will require intensive efforts to maximize the use of mental health support services by students.…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Amir et al, 2008;Britton et al, 2015;Heeren et al, 2015). Based on the evidence that abnormal AB contributes to the development and maintenance of many psychiatric disorders, important efforts have been invested into the development of behavioral interventions aiming to reduce ABs (Hakamata et al, 2010;Lopes et al, 2015;MacLeod and Clarke, 2014). However, while attentional bias modification (ABM) procedures have shown promising behavioral effects, their underlying neurocognitive mechanisms remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it is accepted that, with time, effort, and motivation, individuals can evolve from implicit to explicit behaviors (Cunningham, Zelazo, Packer, & Van Bavel, 2007;Viacava, Weydmann, Tietze, Santolim, & Bizarro, 2016). The opposite is also admitted, but the transition from explicit to implicit behavior seems to depend on repeated exposure to new associations (Lopes, Viacava, & Bizarro, 2015).…”
Section: Cognitive Implicit Measures In Hrmmentioning
confidence: 99%